2015
DOI: 10.3109/13685538.2015.1062980
|View full text |Cite
|
Sign up to set email alerts
|

Connections between lower urinary tract symptoms related to benign prostatic enlargement and metabolic syndrome with its components: a systematic review and meta-analysis

Abstract: A significant amount of epidemiological evidences have underlined an emerging link between metabolic syndrome (MetS) and lower urinary tract symptoms (LUTS) secondary to benign prostatic enlargement a (BPE). We aimed to assess the connections between LUTS and MetS with its components. Meta-analysis were conducted to determine the mean differences (MD) and confidence intervals of IPSS total score, IPSS-voiding, IPSS-storage and prostate volume (PV) in patients with or without MetS. Ln(odds-ratio) were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 54 publications
0
26
0
1
Order By: Relevance
“…We should point out that some studies [21] suggested that the presence of Met S was not significantly associated with moderate to severe LUTS (OR=1.13, p=0.53) and only altered serum triglycerides, an important component of Met S, and diabetes were associated with this risk. Yet, a positive association was noted between number of Met S components and LUTS/bladder outlet obstruction in this study [21]. It is possible that endocrine abnormalities attributed to central obesity and hypertriglyceridemia may play an important role in development or progression of the pathophysiology of lower urinary tract dysfunction [3839].…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…We should point out that some studies [21] suggested that the presence of Met S was not significantly associated with moderate to severe LUTS (OR=1.13, p=0.53) and only altered serum triglycerides, an important component of Met S, and diabetes were associated with this risk. Yet, a positive association was noted between number of Met S components and LUTS/bladder outlet obstruction in this study [21]. It is possible that endocrine abnormalities attributed to central obesity and hypertriglyceridemia may play an important role in development or progression of the pathophysiology of lower urinary tract dysfunction [3839].…”
Section: Introductionmentioning
confidence: 90%
“…A number of studies have suggested that an inverse association exist between serum T levels and LUTS; however, the underlying biochemical and physiological mechanisms by which reduced T levels affect LUTS have yet to be fully delineated [70717273]. A significantly larger prostate volume was reported in men afflicted with Met S [1921747576], however it is unclear if this increase in prostate volume indeed exerts a clinical significance [32]. Met S which was associated with decreased improvement of postoperative symptoms and LUTS after prostate surgery, suggesting interplay of multiple metabolic risk factors contributing to this complex disorder [77].…”
Section: Metabolic Syndrome Testosterone Deficiency and Pathophysiomentioning
confidence: 99%
See 3 more Smart Citations